Results of a Longer Term NDACC Measurements Comparison Campaign at Mauna Loa Observatory - McGee Thomas J.; Twigg Laurence W.; Sumnicht Grant K.; Leblanc Thierry; Barnes John (EPJ Web of Conferences, 2016)
Between November, 2015 and January, 2015, the Goddard Space Flight Center operated a pair of lidar instruments at the NOAA facility at Mauna Loa on the Big Island of Hawaii (Lat. 19.5N, Lon. 155.5 W, Altitude 3.397 km). Measurements were made during six different four week periods during this time period by both the NASA GSFC Stratospheric Ozone Lidar (STROZ) and the Aerosol and Temperature (ATL) lidar. Also making measurements were the JPL Stratospheric Ozone Lidar and the NOAA Aerosol and Water Vapor Lidar. All instruments participate and archive data with the Network for the Detection of Atmospheric Composition Change. Measurement comparisons were made among various instruments in accordance with the standard intercomparison protocols of the NDACC.